2013
DOI: 10.1109/jlt.2013.2252600
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Micro-Laser Formed by Monolithic Integration of a III-V Pillar With a Silicon Photonic Crystal Cavity

Abstract: Abstract-A novel micro-laser configuration formed by integrating an InGaAs/InP pillar with a silicon photonic crystal cavity is proposed and analyzed in detail. Special attention is paid to designing the cavity such that it can accommodate large-size pillars without performance compromise. The Purcell effect is studied and predicted to be significant because of the close interaction between the cavity modes and the gain medium. An overall quality factor as high as 1 and a spontaneous emission factor close to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Analogous values for the absolute reflection coefficients of the different modes have been demonstrated. Three-dimensional FDTD calculations also show the impact of length on the Q factor of the resonant modes (Table 2), and cavity lengths greater than 5 µm favor the creation of strong resonant modes [98]. Recently, it has been demonstrated that a single nanowire cavity with a triangular cross section lying on an SiO 2 substrate [90] can also sustain high-Q FP resonance, with Q close to 500 for the TE-like mode.…”
Section: (A) Waveguiding Mechanism and Bare Resonatorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Analogous values for the absolute reflection coefficients of the different modes have been demonstrated. Three-dimensional FDTD calculations also show the impact of length on the Q factor of the resonant modes (Table 2), and cavity lengths greater than 5 µm favor the creation of strong resonant modes [98]. Recently, it has been demonstrated that a single nanowire cavity with a triangular cross section lying on an SiO 2 substrate [90] can also sustain high-Q FP resonance, with Q close to 500 for the TE-like mode.…”
Section: (A) Waveguiding Mechanism and Bare Resonatorsmentioning
confidence: 89%
“…single nanowire with a dielectric constant close to that of ZnO, GaN, and CdS at the lasing frequencies, in the more realistic case of a nanowire standing on a substrate [98]. Quality factors up to several hundreds can be achieved for both the HE 11 and TE 01 modes in appropriately sized cavities.…”
Section: (A) Waveguiding Mechanism and Bare Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, lasing has been demonstrated in numerous wavelength and sub-wavelength scale structures, including dielectric micro-discs [1][2][3][4], photonic crystals [5][6][7][8][9], nanowires [10,11] and nanorods [12], nano-membranes [13][14][15], micro-pillars [16][17][18], and metal-clad nano-cavities [19][20][21][22][23][24]. While all these devices enable fundamental research of various nanoscale phenomena [25][26][27], the design and analysis of nanolasers have focused almost exclusively on the optical mode, i.e., pure electromagnetic (EM) consideration, usually at 4.5 K, 77 K and room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Since the observation of the Purcell effect in semiconductor cavities, lasing has been demonstrated in numerous wavelength-and subwavelength-scale structures. These structures include dielectric microdisks [16][17][18][19], photonic crystals [10,[20][21][22][23], nanowires [24,25], nanomembranes [26][27][28], micropillars [29][30][31], and metal-clad cavities [13,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%